IMPLEMENTASI APLIKASI BANGKIT DALAM VALIDASI DAN VERIFIKASI ANGKA KEMISKINAN - Hidayat, Muh. Ryan Rahmatul (Institut Pemerintahan Dalam Negeri (IPDN), 2024)
Poverty is a condition in which basic human needs, such as food, health, education, and employment, are not adequately met, thus hindering an individual's ability to survive and develop their lives. In Majalengka Regency, the problem of poverty has been identified with a percentage reaching 11.21%, while the total population is around 1.35 million people. This study aims to explore the characteristics of poverty in more depth and to verify and validate data on the poor population, especially in Lemahsugih District. The research method used is the qualitative descriptive method. In addition, field observations and interviews were also carried out using the BANGKIT application as a means to determine the final poverty score based on certain indicators. This application allows researchers to analyze the dimensions of poverty comprehensively and obtain a deeper picture of the socio-economic conditions of the local community. The results show that Lemahsugih District has 3,934 Heads of Families (KK) who have been recorded as poor families and are the main targets of verification and validation. Through this process, it is hoped that a more accurate understanding will be obtained regarding the causes, dynamics, and distribution of poverty in the area. Thus, the findings of this study are expected to be the basis for formulating more targeted public policies, increasing the effectiveness of poverty alleviation programs, and strengthening collaboration between local governments, social institutions, and communities in poverty alleviation efforts in Majalengka Regency, especially in Lemahsugih District.